2020
DOI: 10.1103/physrevb.101.180501
|View full text |Cite
|
Sign up to set email alerts
|

Momentum-resolved measurement of electronic nematic susceptibility in the FeSe0.9S0.1 superconductor

Abstract: Unveiling the driving force for a phase transition is normally difficult when multiple degrees of freedom are strongly coupled. One example is the nematic phase transition in iron-based superconductors. Its mechanism remains controversial due to a complex intertwining among different degrees of freedom. In this paper, we report a method for measuring the nematic susceptibly of FeSe 0.9 S 0.1 using angle-resolved photoemission spectroscopy (ARPES) and an in-situ strain-tuning device. The nematic susceptibility … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Nevertheless, if confirmed by other experimental measurements, this could be the most direct evidence for a d xy Lifshitz transition. A similar observation has also been made for the sulphur doped FeSe 0.9 S 0.1 system [22,23].…”
Section: Experimental Evidence For Non-local Dxy Nematicitysupporting
confidence: 82%
See 1 more Smart Citation
“…Nevertheless, if confirmed by other experimental measurements, this could be the most direct evidence for a d xy Lifshitz transition. A similar observation has also been made for the sulphur doped FeSe 0.9 S 0.1 system [22,23].…”
Section: Experimental Evidence For Non-local Dxy Nematicitysupporting
confidence: 82%
“…However, it has become increasingly apparent that nematic order derived purely from a degeneracy breaking of the d xz and d yz states is unable to account for many of the experimental properties being observed within this material. Most notably, nematic ordering of the d xz and d yz orbitals predicts a Fermi surface topology which consists of one hole pocket and two electron pockets [15][16][17][18], whereas ARPES measurements of the nematic state of FeSe report the observation of one hole pocket and a single electron pocket [19][20][21][22][23][24]. This incorrect description of the Fermi surface has also made understanding the superconducting properties of FeSe challenging [10,11,25,26], without the addition of alternative anisotropic mechanisms, such as highly anisotropic orbital selective quasiparticle weights, [26,27] or orbital selective spin fluctuations [25].…”
Section: Introductionmentioning
confidence: 99%
“…ARPES studies in thin films of FeSe indicate that the tensile strain promotes significant shifts of the electron bands that can lead to the formation of highly-mobile Dirac carriers 45 . Shifts of 2-3 meV under tensile strain can reduce the size of both electron and hole pockets 46 ; the inner electron band could eventually disappear with increasing the strength Opposite trends are found for tensile strain which can be detected from the constant temperature strain loops in Fig. S4d.…”
Section: Resultsmentioning
confidence: 79%
“…Firstly, can we experimentally identify the exact conditions when one of the electron pockets in the tetragaonal state appears or disappears from the Fermi level? So far, this has remained slightly ambiguous, with some experiments claiming a gradual disappearance of the electron pocket [37] and others claiming a Lifshitz transition around 70 K [35,36,67].…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…In an orthorhombic crystal, conventional ARPES experiments measure a superposition of two perpendicularly orientated crystallographic domains, which doubles the number of bands observed in the experimental data and creates ambiguity about which bands arise from which domain. For this reason, a recent focal point of research has involved overcoming this technical challenge of orthorhombic domains, for example by applying uniaxial strain [28,[34][35][36][37][38][39][40] or using NanoARPES [41] or scanning tunneling microscopy [14,15,42,43]. The conclusion from these measurements have been unanimous, and have revealed that within the nematic state the Fermi surface of FeSe consists of one hole pocket and one electron pocket.…”
Section: Introductionmentioning
confidence: 99%